2017
DOI: 10.4103/1119-3077.196988
|View full text |Cite
|
Sign up to set email alerts
|

Otorhinolaryngological emergencies in a Tertiary Hospital in Port Harcourt

Abstract: ORL emergencies are common. The pediatric age group is the most affected; foreign body and trauma comprise the commonest emergency in our environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
1
2
0
2
Order By: Relevance
“…The finding is however similar to report from a study done southern part of Nigeria [18]. Geriatric otorhinolaryngologic emergency conditions are similar to other forms of emergencies with the mostly early presentation, common presentation during the day time and were referred mainly by general practitioners or casualty officers [25].…”
Section: Discussionsupporting
confidence: 87%
“…The finding is however similar to report from a study done southern part of Nigeria [18]. Geriatric otorhinolaryngologic emergency conditions are similar to other forms of emergencies with the mostly early presentation, common presentation during the day time and were referred mainly by general practitioners or casualty officers [25].…”
Section: Discussionsupporting
confidence: 87%
“…In a study performed by Ibekwe et al, children from 0-10 years constituted the maximum number of cases 31.02% and the least being patients between the age of 61-70 years. 7 Barman et al also found that their majority of patients were children in their first decade. 8 Foreign body aspiration/ingestion/insertion were the most common emergency (74.6%) followed by trauma (23.7%) in our study.…”
Section: Discussionmentioning
confidence: 96%
“…Las lesiones por cuerpos extraños son una causa común de urgencia ORL y se presentan predominantemente en edad pediátrica. Otras causas incluyen lesiones traumáticas a nivel facial y cervical que pueden comprometer el tracto aerodigestivo, trastornos hemorrágicos y procesos inflamatorios agudos junto con sus complicaciones que podrían considerarse emergencias graves por requerir una intervención inmediata 8,9 .…”
Section: Introductionunclassified